Sosialisasi Dan Pengolahan Eceng Gondok Menjadi Pakan Ternak - Rina Dian Rahmawati; Aufia Aisa; Siti Fathimah Al Fathiyah; Dita Hafizah; Aan Fakhrur R; Arta Zulian Effendi; Dania Fia Anggrena; Fadilah Dewi Sinta (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2024)
The use of water hyacinth as fodder in Tapen, Kudu is one of the innovative solutions to overcome environmental problems while improving the welfare of livestock farmers. The purpose of holding the socialization of the use of water hyacinth is to provide the community with an understanding of the processing of water hyacinth into fodder. The method used in this community service program is a discussion in the form of providing materials and questions and answers regarding the importance of using water hyacinth as fodder. The targets of this economic program are farmer groups, livestock farmers and youth of Tapen. As a result of this community service, people who previously saw water hyacinth only as a problem are now able to see it as a useful resource.